THU0401 Global longitudinal strain as early predictor of systolic dysfunction in systemic sclerosis. (12th June 2018) - Fischetti, C.; Guerra, F.; Ferrarini, A.; Zuliani, L.; Stronati, G.; Fraticelli, P.; Danieli, M.G.; Capucci, A.; Gabrielli, A.
Abstract : Background: Systemic sclerosis (SSc) is a chronic autoimmune disease of unknown etiology, characterised by microvascular abnormalities, immune abnormalities and progressive cutaneous and internal organs fibrosis. Subclinical heart disease in SSc patients is common but difficult to detect through conventional imaging. Objectives: We sought to evaluate speckle-tracking derived global longitudinal strain (GLS) as an early marker of subclinical systolic dysfunction in patients with SSc. Methods: We enrolled 52 patients with SSc and 52 age and gender matched controls. Patients with structural heart disease, heart failure, atrial fibrillation or pulmonary hypertension were excluded. An echocardiographic exam was performed for all patients, and standard and specke-tracking derived variables for the systolic and diastolic function of the left ventricle (LV) and right ventricle (RV) were acquired. SSc variant, antibodies pattern, cardiovascular risk factors and involvement of other organ systems were recorded. Results: Common parameters of left and right systolic function did not differ between SSc patients and controls and were on average well above the cut-off for normality (all p=NS). LV and RV GLS were significantly impaired in patients with SSc when compared to healthy controls (−19.2% vs. −21.1%; p=0.009 and −18.2% vs. −22.3%; p=0.012 respectively). In patients with SSc, GLS impairment was greater in basal segments when compared to midventricular and apical ones and homogeneous between the endo-, meso-, or epicardial layers of the RV, while LV showed an eccentric pattern with the epicardial layers mostly impaired. Using −20% as a cut-off for GLS, SSc patients had a 2.5-fold increased risk of subclinical LV systolic impairment (OR 2.5; 95% CI 1.1–5.5; p=0.027) and a 3.3-fold increased risk of subclinical RV systolic impairment when compared to age and gender matched controls (OR 3.3; 95% CI 1.4–7.7; p=0.004). Conclusions: While traditional parameters are ineffective in detecting subclinical systolic impairment, a reduced GLS is common in patients with SSc and is significant for both LV and RV. While GLS impairment recognises a basal-apical gradient, transmural heart involvement seems different between RV and LV, suggesting a different mechanism of disease between the two ventricles. Disclosure of Interest: None declared